Respuesta :

Answer:

(See bolded numbers)

Factoring -1 out of negative numbers:

11) (-6) • (3)= (-1 • 6) • 3= -16 • 3= -18

-6 is the negative number here and factoring out -1 from -6 will give us -1(6). In the second last step, multiply 6 and 3 together then multiply the product by -1.

-1(6 ×3)= -1(18)= -18

12) (-4) • (-8)= (-1 • 4) • (-1 • 8)= 1 4 • 8= 32

Multiplying 2 negative numbers will give us a positive number. The 3rd step is 1 as (-1)(-1)= 1.

13) (-9) • (-5)= (-1 • 9) • (-1 • 5)= 195= 45

14) (2) • (-8)= 2 • (-1 • 8)= -128= -16

Negative numbers are numbers with a negative sign and are numbers less than zero. Factoring -1 out of negative numbers will leave us with the positive number.